The Organization of European Multinationals - Dalia Marin; Linda Rousová (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
Recent literature on international trade has established that the most productive firms become multinationals. But our data reveal a startling variation in productivity levels of foreign affiliates across the countries in Eastern Europe of the same European multinational parent firms suggesting that not all multinationals transplant their home productivity advantage to the new EU Member States and Emerging Europe. One candidate for this startling difference in productivity levels among foreign affiliates is the ability of European multinationals to transport their business model abroad. This paper examines the conditions under which European multinationals give autonomy to their subsidiaries and delegate authority to them. We also analyse the conditions under which European multinationals transplant their business model to Eastern Europe. We collect original and unique matched parent and affiliate data on the internal organization of 660 German and Austrian parent firms and 2200 of their subsidiaries in Eastern Europe including the former Soviet Union. We test the hypothesis that the ability of European multinationals to transplant their business model to foreign affiliates is determined by the organization of European multinationals on the one hand and the market environment their affiliate firms face in Eastern Europe on the other hand. We show that the business culture of parent firms accounts for about 50 percent of the variation of the organization of subsidiaries, while the market environment of subsidiaries contributes the rest.
urn:nbn:de:bvb:19-epub-12453-0
Keywords: F; F23; D21; L22; O1; 330; International Trade and Organizations; Multinational firm with internal hierarchies; Empirical test of the theory of the firm; Technology transfer to Eastern Europe; Organizational transfer across countries; Multinationales Unternehmen; Organisationsstruktur; Europäisch; Ausländische Tochtergesellschaft; Produktivität; Unternehmenskultur; Deutsch; Österreichisch; Osteuropa; Deutschland; Österreich